المصطلح البلاغي في التراث العربي القديم "منهاج البلغاء وسراج الأدباء لحازم القرطاجني أنموذجا - شادي, عبد الرشيد; بن صالح, محمد (جامعة الوادي - University of Eloued, 2020)
ملخص: شكلت قضية المصطلح في التراث العربي حيزا هاما من اهتمامات النقاد والبلاغيين العرب قديما وحديثا وذلك لكونه الدعامة الأساسية التي تحكم الشعر، النقد والبلاغة. لذلك يسعى هذا البحث إلى تناول قضية مهمة من قضايا الخطاب البلاغي العربي، وهي قضية المصطلح البلاغي عند واحد من أهم أعلام النقد والبلاغة العربيين وهو حازم القرطاجني من خلال كتابه "منهاج البلغاء وسراج الأدباء". وهو ما حاولنا الوقوف عليه من خلال التعرض إلى ضبط المفهوم اللغوي والاصطلاحي للمصطلح، وإبراز أهم طرائق وآليات وضعه، وكذا رصد جملة من المصطلحات البلاغية لفكر الرجل في منهاجه، وبهذا تكون هذه الدراسة قد كشفت عن ضرورة قراءة التراث العربي واستنطاقه، وإضاءة جوانبه المهمة خاصة التي تعكس التميز والإبداع قديما وحديثا، فقراءة المصطلح البلاغي عند حازم تنم عن رؤية حديثة وواعية، كفيلة بتأصيل إطار مصطلحي عربي شامل. Abstract The issue of terminology, in the Arab heritage, formed an important area in the Arab ancient and contemporary critics’ and rhetoricians’ interest, since it’s the main foundation governing poetry, criticism, and rhetoric. Therefore, this research looks for addressing an important issue in the Arab rhetorical discourse, which is the rhetorical terminology, for Elqartajani, through his book “The Rhetoricians’ Method and The Authors’ Light. ” We attempt to address setting the linguistic and terminological concept of terminology, and show the important ways and mechanisms for generating it, as well as monitoring a group of rhetorical terms in Hazem Elqartajani’s intellectuality and method. So, this study has revealed the necessity of reading and interrogating the Arab heritage, as well as enlightening its important sides, especially those of excellence and creativity in the past and the present time. Reading the rhetorical terminology, in Hazem’s works, shows a modern mindful vision that ought to indigenize an Arab comprehensive terminological framework. one of the Arab flags in criticism and rhetoric who’s Hazem
مقال
Keywords: الخطاب؛ المصطلح؛ البلاغة؛ المنهاج؛ التراث؛ النحت؛ الاشتقاق.